The Usefulness of Early Effect Biomarkers in Monitoring Occupational Exposure to Hexavalent Chromium - Afonso, Catarina (2020)
Introduction: In the frame of the Project HBM4EU (https://www.hbm4eu.eu/) a biomonitoring study is being conducted across Europe to characterize occupational exposure to hexavalent chromium [Cr(VI)], a recognized human lung carcinogen. Herein we present the results of biomarkers of exposure and effect characterized in a group of workers from a Portuguese aircraft maintenance company, where Cr(VI) replacement is not expected in the near future. Methods: All participants signed an informed consent and responded to a questionnaire to collect contextual information. Cr(VI) exposure was assessed by the analysis of personal air samples; total Cr was measured in urine and blood samples from 50 workers and 26 controls. The effects biomarkers included the alkaline comet assay and the cytokinesis-block micronucleus assay in blood in leukocytes. Results: The concentrations of Cr in the air samples were variable, depending on the activities performed. Noteworthy, workers engaged in painting exterior surfaces with Cr(VI)-reach paints were exposed to the highest Cr(VI) levels. Results from biomonitoring confirmed the occurrence of internal exposure. Furthermore, significantly increased micronuclei frequencies (p < 0.001, Fisher’s exact test) and DNA damage levels were identified in leukocytes from workers comparatively to controls. Interestingly, among the painters showed up a group of 6 workers who were exposed to a mixture of Cr, organic solvents, silica, and other chemicals and who displayed an elevated level of micronucleated cells comparatively to matched controls. Conclusions: An association between Cr(VI) exposure and genotoxicity biomarkers was found, raising concern about a potentially increased cancer risk. Furthermore, these results suggest that the effect biomarkers selected are useful to strengthen the exposure data, in that more exposed or vulnerable groups can be more reliably detected. This is relevant to allow the prioritization of occupational hygiene and risk management measures implementation in the workplace.